Contar para curar: estadísticas y comunidad médica en Argentina, 1880-1940 Counting to cure: statistics and the medical community in Argentina, 1880-1940 - Claudia Daniel (História, Ciências, Saúde: Manguinhos)
Analiza los vínculos entre el grupo profesional médico y la institucionalización de la estadística en la Argentina del período 1880-1940. Presenta los inicios de las estadísticas médicas y demográficas en el país, vinculados con los ideales y proyectos higienistas de fines del siglo XIX. Describe la posterior organización y estabilización de una agencia estatal encargada de producir esas cifras que tuvo la particularidad de ser dirigida por una mujer durante varias décadas. Indaga el problema planteado en relación con la formación de cuadros técnicos para la estadística pública. Explora las fuentes de tensión y las polémicas en torno al método numérico que se entablaron en la comunidad médica, reconstruidas a partir de las revistas especializadas. The article analyzes the links between the professional medical community and the institutionalization of statistics in Argentina in 1880-1940. It begins with the initial period of medical and demographic statistics in Argentina, which bore ties to late nineteenth-century hygienist ideals and projects. It then describes the later organization and consolidation of a state agency responsible for producing these data, which, interestingly enough, was headed by a woman for several decades. The challenges encountered in training technical staff to produce public statistics are also examined. Based on information found in specialized magazines, the analysis likewise explores the tensions and controversies that arose within the medical community over the use of the numerical method.